The Caucasus as a «school of war» for the Russian army (on the assessment of the experience of the first half of the 19th century) - Yu. Yu. Klychnikov (Гуманитарные и юридические исследования)
The development of the Caucasus by Russia was not without the use of armed forces to fight the mountain peoples. They did not want to obey the laws of the empire and launched a war against it, effectively using the advantages that the natural environment of the region gave them. For the Russian troops, the local natural and climatic situation was unusual, which affected the effectiveness of the conduct of hostilities. The enemy was well adapted to fight in war conditions in mountainous and wooded areas. It required a significant change both in the tactics and strategy of warfare, and in the training of personnel and their equipment. More attention had to be paid to the arrangement and protection of communications, which became one of the priorities of the command. The troops were involved in the construction of roads and felling clearings through difficult areas of the territory. Highlanders skillfully used ambushes, surprise attacks, skillfully used natural shelters as fortifications. Under the circumstances, individual regiments were specialized for operations in specific landscape and climatic conditions, which made it possible to reduce losses during combat clashes with the enemy. It was necessary to adopt the military experience of the opponent, often acting the way the highlanders themselves did. All this made it possible to end the prolonged confrontation and break the resistance of the enemy.